تأثير الطلاقة في قراءة القرآن على الطلاقة في مهارة الكلام بمدرسة البهجة القرآنيّة الإسلامية الثانوية شربون - عبد العزيز, عمر; عارفة, زكية; نصر الله, نصر الله (Mayada: al-Multaqa al-Ilmy al-Alamy lil-Dirasat al-Arabiyah, 2024)
Reading the Qur’an is not only a profound act of worship, but also a continuous effort to practice speech skills. This research aims to determine the effect of fluency in reading the Qur’an on the proficiency of fluency in speaking skills for eleventh-grade students at Al Bahjah Al-Qur’an Islamic Secondary School Cirebon. This research uses the Expost Facto Quantitative method with a correlational type of research. The sample used is IX grade students, a total of 44 students. The data collection technique is giving oral tests to the students, which consist of verbal tests of reading the Qur’an and speaking skills in Arabic. To analyze the data, the researcher uses a simple linear regression test. The results showed an effect between fluency in reading the Qur’an and fluency in speech among eleventh-grade students at AlBahjah Al-Qur’anic Islamic Secondary School Cirebon with a moderate correlation interpretation. Based on these values, students should be accustomed to the habit of speaking Arabic in daily life and also to be supported by teachers to operate the Arabic language environment. إن قراءة القرآن ليست عبادة عميقة فحسب، بل هي جهد متواصل لممارسة مهارات الكلام. الغرض من هذا البحث هو لمعرفة تأثير الطلاقة في قراءة القرأن على الطلاقة في مهارة الكلام لطلاب الصف الحادي عشر بمدرسة البهجة القرآنيّة الإسلامية الثانوية شربون. تستخدم هذا البحث المنهج الكمي بالأمر الواقع  Expost Facto Quantitative مع نوع البحث الارتباطي. العينة المستخدمة جميع طلاب الصف الحادي عشر بإجمالي 44 طالبا. تقنية جمع البيانات المستخدمة هي إعطاء اختبارات الشفوية للطلاب التي تتكون من اختبارات شفهية لقراءة القرآن ولمهارات الكلام باللغة العربية. لتحليل البيانات يستخدم الباحث اختبار الانحدار الخطي البسيط. أظهرت نتائج أن وجود تأثير بين الطلاقة في قراءة القرآن على الطلاقة في الكلام لدى طلاب الصف الحادي عشر بمدرسة البهجة القرآنيّة الإسلامية الثانوية شربون بتفسير ارتباط معتدل. بناء على هذه القيم، يجب أن يكون تعويد يقوم به الطلاب على عادة الكلام باللغة العربية في اليومية وأيضا إلى دعم من المعلمين لتشغيل بيئة اللغة العربية.